2021
DOI: 10.3390/ijerph18158204
|View full text |Cite
|
Sign up to set email alerts
|

Safely Managed On-Site Sanitation: A National Assessment of Sanitation Services and Potential Fecal Exposure in Indonesia

Abstract: Sustainable Development Goal target 6.2 calls for universal access to adequate and equitable sanitation, setting a more ambitious standard for ‘safely managed sanitation services’. On-site sanitation systems (e.g., septic tanks) are widely used in low- and middle-income countries (LMICs). However, the lack of indicators for assessing fecal exposure risks presents a barrier to monitoring safely managed services. Furthermore, geographic diversity and frequency of disasters require a more nuanced approach to risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Previous studies have reported discharge of containment effluent to the environment as a common practice in India, with about 72% of containment systems discharging effluent to open drains, especially in the urban environment ( Dasgupta et al, 2019 ). This study and other studies in Dhaka, Bangladesh ( Amin et al, 2019 ) and Indonesia ( Odagiri et al, 2021 ) have found this practice to contribute to the release of faecal pathogens to the environment, constituting a clear public and environmental health hazard. However, our findings suggest that, where feasible, changing from the household fully-lined tanks with effluent pipes to the environment to effectively the same system discharging to soakaways would yield a 1.8 Log 10 reduction in the average combined daily per capita E. coli release.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have reported discharge of containment effluent to the environment as a common practice in India, with about 72% of containment systems discharging effluent to open drains, especially in the urban environment ( Dasgupta et al, 2019 ). This study and other studies in Dhaka, Bangladesh ( Amin et al, 2019 ) and Indonesia ( Odagiri et al, 2021 ) have found this practice to contribute to the release of faecal pathogens to the environment, constituting a clear public and environmental health hazard. However, our findings suggest that, where feasible, changing from the household fully-lined tanks with effluent pipes to the environment to effectively the same system discharging to soakaways would yield a 1.8 Log 10 reduction in the average combined daily per capita E. coli release.…”
Section: Discussionsupporting
confidence: 58%
“…This is in alignment with the well-established fact that some partial treatment of excreta and inactivation or removal of E. coli occurs during safe containment of excreta ( Feachem et al, 1981 ; Franceys et al, 1992 ; Mara, 1996 ). Other studies ( Odagiri et al, 2021 ; Maxcy-Brown et al, 2021 ) have also found that the direct discharge of black-water to the environment is a common practice in India and elsewhere, which we believe results in the substantial release of faecal pathogens to the environment, and a substantive public health hazard. We observe from our data in Fig.…”
Section: Discussionmentioning
confidence: 55%
“…That could be because the respondents are over-claimed that their septic tank is regularly emptied which could not be confirmed at that moment. In the Indonesian context, a household septic tank that is regularly emptied, e.g., every three to five years, indicates a safely managed sanitation facility 49 . A closer inspection should be conducted to confirm this finding.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Unfortunately, sustainable implementations are still grossly lacking worldwide, and exposure risks to public health due to non-functional service chains remain high. For example, "uncontained" septic tanks and containment outflows that discharge directly to the urban environment (Odagiri et al, 2021), illegal dumping, and inadequate treatment (Okaali et al, 2022). However, the importance of a FSM service chain to protect public health is gaining recognition, and as a result the demand for infrastructure and services to manage fecal sludge is increasing (Vijayan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%